New Microstrip Resonator of Nanostructured Materials in a Liquid-Crystal-Based Phase Shifter - Attoui, A.; Boualleg, A.; Redadaa, S. (Наносистеми, наноматеріали, нанотехнології, 2017)
In this article, we study the properties of 6 nm liquid crystal (LC)–NsM system that forms highly stable solutions in the nematic liquid crystal 4-cyano-4-n-pentylbiphenyl (5CB). The nanostructure is covalently functionalized with 4-sulfanylphenyl-4-[4 (octyloxy) phenyl] benzoate (SOPB), which resembles the structure of the 5CB molecules. The use of LCs as an NsM with phased array antennas is for steering the beam pattern electronically with high effectiveness, managing to get minimum side-lobe levels and narrow beam widths. Normally, phase shifters are the devices in a phased array antenna that allows the radiated beam to be steered in the direction. The objective of this work is to investigate a phase shifter in a linear antenna array for angle scan. A microstrip antenna array is used since it is simple to be designed and fabricated. Ansoft Designer Software is used to simulate the phase shifter for applications to antenna array with LC directed synthesis of NsM. In our paper, we present a new external command with a new influence of the static magnetic bias field of liquid crystal for shifted radiation pattern.